Sexual decision-making: an exploratory interview study of Cambodian adolescents - Park, Gloria; Yang, Youngran (Frontiers in Reproductive Health, 2024)
IntroductionThe rate of sexual activity among adolescents is very high, with serious repercussions such as human immunodeficiency virus (HIV) and sexually transmitted diseases. Understanding the factors that influence adolescents’ engagement in sexual activity is crucial for promoting healthy sexual attitudes and behaviors in schools, sex education programs, communities, and families. This study aimed to examine the factors influencing sexual decision-making among Cambodian adolescents.MethodsIn accordance with the Standards for Reporting Qualitative Research (SRQR), this study used a descriptive qualitative methodology with individual interviews. The participants in the study were 30 Cambodian adolescents (15 males and 15 females) who were all unmarried and sexually active. They were recruited using various methods, including social networking services, and interviewed to explore their sexual decision-making processes.ResultsThe analysis revealed that the decision-making process was influenced by both internal and external factors. Internal factors included sexually explicit Internet material and arousal from sexy outfits, while external factors included foreign vs. Khmer culture, the surrounding environment including community, peers, and family, and educational advice received at school. Gender differences were noted in responses to stimuli like sexy outfits and perceptions of cultural norms.ConclusionsThis study underscores the complexity of adolescent sexual decision-making in Cambodia. It highlights the need for sex education that is not only comprehensive but also culturally sensitive, addressing the diverse influences on these adolescents. Future research should include a broader demographic group, including rural adolescents, to gain more comprehensive insights.Implications for practiceThis study uncovers how cultural norms, peers, and the media impact sexual behaviors, emphasizing the significant gender differences in these aspects. The findings shed light on the necessity of culturally sensitive and comprehensive sex education and the urgent need for tailored approaches to health promotion and education.